A Preliminary Work on the Intellectual and Civilisational Dimensions of the Al-Jawaib Based on Ottoman Sources - Ozay, Mehmet; Faris, Waleed Fekry (Journal of Al-Tamaddun, 2025)
This study was an investigation of the relationships between Ahmad Faris al-Shidyaq, editor of the al-Jawaib (Circulating News), an Arabic newspaper published in İstanbul, his son Selim Faris, and the Ottoman authorities, utilising only Ottoman archival documents, in particular, the Presidential Ottoman Archives (BOA) between 1859 and 1887. Since this paper is the initial one of many, the complete biography of Ahmad Faris and the content analysis of al-Jawaib were not discussed, but only the relevant issues within the aforementioned period. And it also explored the partial life of Ahmad Faris al-Shidyaq. Although the editor and his newspaper are well-known, certain aspects of the relationship between Ahmad Faris and the Ottoman authorities in the Ottoman archival document have yet to be elaborated on. This brief study examined the correspondences between Ahmad Faris and the Ottoman authorities descriptively without delving into details. Since these archival documents were generally intact, it seemed to be worth analysing in this article. Before studying the journalistic and intellectual contents and contexts of the al-Jawaib, it would be valuable to see the development of the relationship between Ahmad Faris and the Ottoman authorities. Several fundamental questions come to mind, and it is believed that the answers to these would be helpful in comprehending other aspects in the later stages of the al-Jawaib publication of almost 25 years. This research-based paper applied historical archival study with an interpretative approach.